A host-feeding wasp shares several features of nitrogen management with blood-feeding mosquitoes. (October 2018) - Richard, Romain; Foster, Stephen; Giron, David; Casas, Jérôme
Abstract: Adult feeding on hosts is common among parasitic wasps. The ingested host fluid is rich in nutrients, especially proteins. A study on Eupelmus vuilleti (Hymenoptera: Eupelmidae), a host-feeding parasitoid of larvae of Callosobruchus maculatus (F.) (Coleoptera: Bruchidae), showed that the carbohydrates (maybe lipids) but not proteins, gained from host feeding accounted for the increased egg production. Thus, host protein is probably utilized for general adult metabolism, allowing conservation of carbohydrate and/or lipid resources for direct allocation to oocytes. In that case, there should be increased N excretion by female parasitoids. To test this, we studied the dynamics of excretion in E. vuilleti with and without host exposure. The aim of this work was threefold: (i) to identify the major N-containing compounds in adult excreta, (ii) to assess whether protein consumption during host feeding increased the amount of N excreted, and (iii), if so, to compare the increase in N excreted with the amount taken in during a single host feeding. We found that uric acid is the predominant N-containing metabolite in excreta, although small quantities of urea and traces of allantoin were also found. A calculation of the N budget showed that the extra quantity of N excreted following a host meal corresponds to the quantity ingested, confirming that host-feeding in this species offers little or no net quantitative benefit in N allocation to oocytes, although the allocation of specific amino acids from host feeding cannot be discounted. Interestingly, host-feeding in parasitoids appears analogous to vertebrate blood-feeding in mosquitoes, both in terms of the N-containing compounds excreted and the offset of acquired N to metabolism, rather than to oocytes. Further comparative and detailed investigations of N excretion in insects living on other N-rich fluids might establish further metabolic commonalities.